Consistent sleep onset and maintenance of body weight after weight loss: an analysis of data from the NoHoW trial - Larsen, Sofus C. (2020)
Copyright: © 2020 Larsen et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.